ADJUSTMENT OF MARKET STALL AND KIOSK RENTAL RATES FOR PT. TANJUNGPINANG MAKMUR BERSAMA - Suryadi; Fatahurrazak; Oksep Adhayanto; Bismar Arianto (Mimbar Hukum, 2023)
Abstract Policies of decentralization and regional autonomy have provided opportunities for regional governments to increase regional revenue sources through local ownership revenue (PAD). One source of PAD is the distribution of profits (dividends) obtained through regionally owned enterprises (BUMD). This study simulates the calculation of rental rates for kiosks, tables, booths, and buildings managed by PT. Tanjungpinang Makmur Bersama (TMB) which is a BUMD owned by the Government of Tanjungpinang City. With this rental rate adjustment, it is expected to increase TMB's revenue,which in turn, will increase Tanjungpinang City's PAD and encourage PT. TMB to become an independent BUMD. This study was conducted in a quantitative descriptive manner using a case study research strategy (CSR). Based on this study, four simulations were performed to calculate the rental rate adjustments. In the first simulation, increasing the price of kiosks/tables/shops by 146.90% will provide dividends to the Tanjungpinang City Government of IDR 500 million a year, excluding other businesses. The second simulation, by increasing the price of the kiosk/table/shop by 99.14%, will provide a dividend of IDR 100 million per year. In the third simulation, if the price of the kiosk/table/shop increases by 93.17%, it will provide a dividend of IDR 50 million a year, excluding other businesses. In the fourth simulation, if the price rate for the kiosk/table/booth is increased by 87.20%, it will provide a dividend of IDR 0 a year, excluding other businesses. Abstrak Kebijakan desentralisasi dan otonomi daerah telah memberikan peluang bagi pemerintah daerah untuk meningkatkan sumber pendapatan daerah melalui pendapatan asli daerah (PAD). Salah satu sumber PAD adalah pembagian keuntungan (dividen) yang diperoleh melalui Badan Usaha Milik Daerah (BUMD). Penelitian ini melakukan simulasi perhitungan tarif sewa kios, meja, booth, dan gedung yang dikelola oleh PT. Tanjungpinang Makmur Bersama (TMB) yang merupakan BUMD milik Pemerintah Kota Tanjungpinang. Dengan penyesuaian tarif sewa ini, diharapkan pendapatan TMB meningkat yang pada gilirannya dapat meningkatkan PAD Kota Tanjungpinang dan mendorong PT. TMB menjadi BUMD mandiri. Penelitian ini dilakukan secara deskriptif kuantitatif dengan menggunakan strategi Penelitian Studi Kasus yang disebut penelitian studi kasus (CSR). Berdasarkan penelitian ini, empat simulasi dilakukan untuk menghitung penyesuaian tarif sewa. Pada simulasi pertama, kenaikan harga kios/meja/toko sebesar 146,90% akan memberikan dividen kepada Pemerintah Kota Tanjungpinang sebesar Rp500 juta setahun, di luar usaha lainnya. Simulasi kedua, dengan menaikkan harga kios/meja/toko sebesar 99,14%, akan memberikan dividen sebesar Rp100 juta per tahun. Pada simulasi ketiga, jika harga kios/meja/toko naik sebesar 93,17%, maka akan memberikan dividen sebesar Rp50 juta setahun, tidak termasuk usaha lainnya. Pada simulasi keempat, jika tarif harga kios/meja/booth dinaikkan sebesar 87,20% maka akan memberikan dividen sebesar Rp0 setahun, tidak termasuk usaha lainnya.